Short-Term Sensorimotor Deprivation Impacts Feedforward and Feedback Processes of Motor Control - Scotto, Cécile R.; Meugnot, Aurore; Casiez, Géry; Toussaint, Lucette (Frontiers in Neuroscience, 2020)
Sensory loss involves irreversible behavioral and neural changes. Paradigms of short-term limb immobilization mimic deprivation of proprioceptive inputs and motor commands, which occur after the loss of limb use. While several studies have shown that short-term immobilization induced motor control impairments, the origin of such modifications is an open question. A Fitts’ pointing task was conducted, and kinematic analyses were performed to assess whether the motor command and/or motor control were impacted. This Fitts’ pointing task specifically required dealing with spatial and temporal aspects (speed-accuracy trade-off) to be as fast and as accurate as possible. Forty trials were performed on two consecutive days by Control and Immobilized participants who wore a splint on the right arm during this 24 h period. The immobilization modified the motor control in a way that the full spatiotemporal structure of the pointing movements differed: A global slowdown appeared. The acceleration and deceleration phases were both longer, suggesting that immobilization impacted both the planning and the online correction phase. First, the planning of the action may have been less efficient, probably because the internal model of the immobilized limb could not have been updated. Second, immobilized participants may have taken more time to correct their movements to precisely reach the target, as the processing of proprioceptive cues might have been altered.